French Didactique des Mathématiques and Lesson Study: a profitable dialogue?. Issue 3 (13th July 2015) - Clivaz, Stéphane
Abstract : Purpose: – The purpose of this paper is to present French Didactique des Mathématiques (DM) to the Lesson Study (LS) community. Design/methodology/approach: – This theoretical paper presents the origins of DM in the Theory of Didactical Situations (TDS) by Brousseau. It elaborates about didactical engineering, fundamental situation and other fundamental concepts. It briefly presents other Didactique theories: the theory of conceptual fields, the anthropological theory of the didactic, the joint action theory in didactics and the double approach. It considers importance of the (TDS) and influences over teaching of mathematics. This paper finishes by highlighting the ways Didactique and LS could contribute to each other in a profitable dialogue. Findings: – The paper contrasts DM with some LS main features. It highlights the parallels despite fundamental differences in the initial goals of the perspectives. It shows that these differences could lead to productive dialogue by producing more practice-oriented forms of didactical engineering for the first and making teachers' principles for lessons more explicit for the latter. Originality/value: – The paper presents a very quick overview of the parallels between DM and LS. Additionally, this paper gives many accessible references in English for the reader to explore Didactique further.